Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1017/s0029665120005820
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of α-glucosidase inhibition by edible brown algae in the management of type 2 diabetes

Abstract: AbstractPrevalence of type 2 diabetes mellitus has significantly increased in the last three decades and currently affects about 1 in 10 globally. A common therapeutic target for type 2 diabetes is α- glucosidase, an essential enzyme located at the brush border of the small intestinal epithelium. The inhibition of α-glucosidase results in a reduced digestion of carbohydrates and a decrease of postprandial blood glucose. Although, synthetic inhibitors are available in the market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The mammalian α-glucosidase is synthesized in the mucosal brush border of the small intestine, and its major physiological function is to catalyze the digestion of disaccharides and starch which make up a huge percentage of the human diet [145]. The enzyme selectively catalyzes the endonucleolytic or exonucleolytic hydrolysis of various sugars producing monosaccharides, oligosaccharides, or glycosaminoglycans, which increases postprandial blood glucose [146][147][148]. This enzyme is considered a crucial clinical target for the treatment of T2D [149].…”
Section: Alpha-glucosidase Inhibitionmentioning
confidence: 99%
“…The mammalian α-glucosidase is synthesized in the mucosal brush border of the small intestine, and its major physiological function is to catalyze the digestion of disaccharides and starch which make up a huge percentage of the human diet [145]. The enzyme selectively catalyzes the endonucleolytic or exonucleolytic hydrolysis of various sugars producing monosaccharides, oligosaccharides, or glycosaminoglycans, which increases postprandial blood glucose [146][147][148]. This enzyme is considered a crucial clinical target for the treatment of T2D [149].…”
Section: Alpha-glucosidase Inhibitionmentioning
confidence: 99%
“…In the research on diabetes and related diseases, glycosidase has been identified as the key enzyme that regulates blood glucose levels in the human body. Inhibitors of glucosidase activity in the small intestine villi have been found to delay the breakdown and digestion of complex carbohydrates and disaccharides, thereby reducing the absorption of glucose in the intestinal cavity and mainly lowering postprandial blood sugar (Maha et al., 2020). Additionally, inhibiting amylase can effectively balance blood glucose concentration by slowing down the rise of blood glucose after eating, thus lowering overall blood glucose levels (Rane et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of α -glucosidase can reduce the cleavage of glucose from disaccharides or oligosaccharides to inhibit postprandial hyperglycemia [ 4 ]. Therefore, α -glucosidase is a common therapeutic target for the treatment of T2DM [ 5 ]. Currently available α -glucosidase inhibitors, such as acarbose, voglibose and miglitol, have been used to treat T2DM patients.…”
Section: Introductionmentioning
confidence: 99%